Functional identification of DNA demethylase gene CaROS1 in pepper (Capsicum annuum L.) involved in salt stress - Ou, Xuelian; Hua, Qingzhu; Dong, Jichi; Guo, Kexian; Wu, Minghua; Deng, Yinjun; Wu, Zhiming (Frontiers in Plant Science, 2024)
Pepper, which is a widely cultivated important vegetable, is sensitive to salt stress, and the continuous intensification of soil salinization has affected pepper production worldwide. However, genes confer to salt tolerance are rarely been cloned in pepper. Since the REPRESSOR OF SILENCING 1 (ROS1) is a DNA demethylase that plays a crucial regulatory role in plants in response to various abiotic stresses, including salt stress. We cloned a ROS1 gene in pepper, named CaROS1 (LOC107843637). Bioinformatic analysis showed that the CaROS1 protein contains the HhH-GPD glycosylase and RRM_DME domains. qRT-PCR analyses showed that the CaROS1 was highly expressed in young and mature fruits of pepper and rapidly induced by salt stress. Functional characterization of the CaROS1 was performed by gene silencing in pepper and overexpressing in tobacco, revealed that the CaROS1 positively regulates salt tolerance ability. More detailly, CaROS1-silenced pepper were more sensitive to salt stress, and their ROS levels, relative conductivity, and malondialdehyde content were significantly higher in leaves than those of the control plants. Besides, CaROS1-overexpressing tobacco plants were more tolerant to salt stress, with a higher relative water content, total chlorophyll content, and antioxidant enzyme activity in leaves compared to those of WT plants during salt stress. These results revealed the CaROS1 dose play a role in salt stress response, providing the theoretical basis for salt tolerance genetic engineering breeding in pepper.